Factors of employee retention in IT industry - MONICA, DR. BENITA. S.; REDDY, MS. G. SOWMYA (The journal of contemporary issues in business and government, 2020)
Organisations spend a lot of resources for training talented employees and making them worthy, retention of such employees is a crucial task for an organisation. The target of the current study was to research explicit maintenance factors that prompted the authoritative responsibility of high innovation workers. The sample for the data is collected from the 62 expert IT professionals from a reputed IT company in Chennai. The Organizational Commitment Scale and a maintenance factor estimation scale were managed. The most applicable logical variables were pay, work qualities, employee’s assistance and work/life balance strategies, which seemed to impact the improvement of hierarchical responsibility in high innovation employees or representatives. The implications of the study are also examined. The study focuses to help the organizations to determine the retention strategies for the maintenance of employees.